2005
DOI: 10.1007/11567646_25
|View full text |Cite
|
Sign up to set email alerts
|

A C 1 Globally Interpolatory Spline of Arbitrary Topology

Abstract: Abstract. Converting point samples and/or triangular meshes to a more compact spline representation for arbitrarily topology is both desirable and necessary for computer vision and computer graphics. This paper presents a C 1 manifold interpolatory spline that can exactly pass through all the vertices and interpolate their normals for data input of complicated topological type. Starting from the Powell-Sabin spline as a building block, we integrate the concepts of global parametrization, affine atlas, and spli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 20 publications
(28 reference statements)
0
8
0
Order By: Relevance
“…Thus, the evaluation algorithms and other computational procedures are both efficient and robust. They have also showed that any planar spline schemes (defined over an open planar domain) which satisfy the parametric affine invariant property can be straightforwardly extended to manifolds of arbitrary topology within the manifold spline framework [He et al 2006a;He et al 2005;He et al 2006b]. …”
Section: Introductionmentioning
confidence: 99%
“…Thus, the evaluation algorithms and other computational procedures are both efficient and robust. They have also showed that any planar spline schemes (defined over an open planar domain) which satisfy the parametric affine invariant property can be straightforwardly extended to manifolds of arbitrary topology within the manifold spline framework [He et al 2006a;He et al 2005;He et al 2006b]. …”
Section: Introductionmentioning
confidence: 99%
“…The geometric modeling literature on constructing 𝐺 1 /𝐶 1 surfaces is vast, but due to constraints of our problem, only a few constructions are relevant in our context; [He et al 2005;Powell and Sabin 1977] which we rely on, and [Dahmen 1989] being most closely related. We provide more details in Section 5.…”
Section: Related Workmentioning
confidence: 99%
“…(If the interior h of the union of the finite elements is not equal to , then the functions in S h vanish on \ h . Details of construction of C 1 splines on arbitrary topology are in [15,16]). Throughout the paper, for a nonnegative integer k, the standard norm in the Sobolev space H k ( ) is denoted by · k , L 2 ( ) = H 0 ( ); H 1 0 ( ) denotes the space of all functions φ ∈ H 1 ( ) with φ = 0 on ∂ ; C denotes a generic positive constant which may depend on r, but which is independent of h, the time-discretization parameter τ and the exact solution of the partial differential equation.…”
Section: Introductionmentioning
confidence: 99%
“…However, for our nonlinear model problem (1.1) in non-divergence form with diffusion coefficient depending linearly or nonlinearly on the unknown solution, the choice of H 2 trial space is natural. Construction of C 1 splines (and hence H 2 trial spaces) is no longer considered to be difficult even on arbitrary topology, in view of the recent work [15,16] and references therein. In comparison with C 0 finite element Galerkin methods, C 1 smoothness of the H 1 -Galerkin approximate solutions leads to significantly smaller linear systems.…”
Section: Introductionmentioning
confidence: 99%